Efektivitas Pemanfaatan Aplikasi LOCUS GIS dan MAPIT GIS Untuk Pengumpulan Data Pendaftaran Tanah - Muhammad Mahirda Ariwibowo; Suharno Suharno; Wahyuni Wahyuni (Sekolah Tinggi Pertanahan Nasional, 2020)
Abstract: The activity of collecting land registration data is the main stage in the Complete Systematic Land Registration program (PTSL). Nowadays, the acceleration strategy by utilizing information technology such as Locus GIS and Mapit GIS as an android-based application for support land data collection activities has been widely used, both free and paid. Therefore, the factors of effectiveness of the application are important to be considered by the users so that they can be used appropriately and optimally according to user needs. This study aims to explore important matters related to the features owned and their advantages and disadvantages and usability of applications for collecting land registration data. Mix methods were used in this study which combines two approaches, namely qualitative and quantitative approach. The data of this study was collected through interview, observation and questionnaire. The result of this study shows that 1) Application features of Locus GIS and Mapit GIS can be used for land data collection by considering the advantages and disadvantages of each; 2) The results of evaluating the utility test toward both applications for land data collection in accordance with ISO / IEC 9126-1 and ISO / IEC 9126-4 standards shows that it is equivalent to